Colloidal Gold Probe-Based Immunochromatographic Strip Assay for the Rapid Detection of Microbial Transglutaminase in Frozen Surimi. (24th August 2016) - Fan, Daming; Li, Yi; Gu, Zhennan; Huang, Jianlian; Zhou, Wenguo; Zhang, Wenhai; Zhao, Jianxin; Zhang, Hao
Abstract : Adding microbial transglutaminase (MTGase) to frozen surimi to enable the surimi to be sold as a higher-grade product at a higher price defrauds surimi product manufacturers and undercuts legitimate industry prices. Therefore, it is important to develop an accurate method of detecting the presence of MTGase in surimi. In this study, an immunochromatographic strip assay with a colloidal gold antibody probe was successfully developed and used to rapidly and qualitatively detect MTGase in surimi samples. The results were obtained in less than 10 min. The limit for the qualitative detection of MTGase using the immunochromatographic strip assay was identified as 1.0  μ g/mL. The results of the immunochromatographic strip analysis of frozen surimi samples were verified by comparison with the results of a sandwich enzyme-linked immunosorbent assay. The colloidal gold probe-based immunochromatographic strip assay was thus found to be a rapid, economical, and user friendly method of detecting MTGase in surimi.